A novel mutant 10Ala/Arg together with mutant 144Ser/Arg of hepatitis B virus X protein involved in hepatitis B virus-related hepatocarcinogenesis in HepG2 cell lines. Issue 2 (28th February 2016) - Shi, Ying; Wang, Junwei; Wang, Yuhe; Wang, Anna; Guo, Hongliang; Wei, Feili; Mehta, Sanjay R.; Espitia, Stephen; Smith, Davey M.; Liu, Longgen; Zhang, Yulin; Chen, Dexi
Highlights: Amino acid residues 10 and 144 of HBx anchored signature sequence in HCC tissues. A10R-S144R mutation prolonged G1/S transition via regulation of cell cycle arrest. A10R/S144R double-mutation decreased Bax expression and inhibited HepG2 apoptosis. Abstract: Hepatitis B virus (HBV) infection-related hepatocellular carcinoma (HCC) represents a major health problem worldwide. HBV X (HBx) protein is the most common open reading frame that may undergo mutations, resulting in the development of HCC. This study aimed to determine specific HBx mutations that differentiate the central- and para-tumor tissues, and identify their association with HCC development. HBx gene from HCC tumor and para-tumor tissues of 47 HCC patients was amplified, sequenced and statistically analyzed. A novel combination of 2 mutations at residues 10 and 144 was identified which might play a significant role in HCC development. Expression vectors carrying HBx with the specific mutations were constructed and transfected into HepG2 and p53-null HepG2 cells. Compared to wild type (WT) and single mutation of HBx at residue 10 or 144, the 10/144 double mutations strongly up-regulated p21 expression and prolonged G1/S transition in WT- and p53-null HepG2 cells. Apoptosis was also inhibited by HBx harboring 10/44 double-mutation. Binding of 10/144 double-mutant HBx to p53 was lower than WT HBx. Conclusively, the 10/144 double mutation of HBx might play a crucial role in HCC formation.